(untitled) (Baghdad Science Journal, 2018)
This study aims at detecting the differences in genotyping of coding region fusA gene in clinical isolates of Acinetobacter baumannii from Baghdad, Iraq. Collected two hundred clinical samples (50 samples from urine, 50 samples from wound, 50 samples from sputum and 50 samples from otitis infections). Laboratory diagnosis for bacterial isolates carried out by some biochemical tests and confirmed by using VITEK- 2 compact system. The results appeared that twenty isolates of Acinetobacter baumannii in all these samples. Genotyping study was performed of coding region fusA gene of the extracted genome of all bacterial isolates and used specific primers in achieved amplification process of this target gene. DNA sequencing of this gene and alignment of sequencing in NCBI was achieved and drew phylogenetic tree by using Geneious 9 software among locally isolates alone and then among locally isolates and high identity global isolates in GenBank. The results in phylogenetic tree of fusA gene in locally isolates showed 4 groups of isolates included more than one source of isolation. The results in phylogenetic tree of the locally and global isolates showed that are four different groups and each group included some locally isolates and global isolates except group A (AE_22, AE_26) and group E (AE_35, AE_32, AE_33) that not identity with global isolates. The nucleotides sequence of fusA gene from localized isolate (AE_35) was registered in national GenBank under accession number (LOCUS KY818057) and protein ID "ARV90995.1.